2020
DOI: 10.14814/phy2.14389
|View full text |Cite
|
Sign up to set email alerts
|

Continuous reduction in cerebral oxygenation during endurance exercise in patients with pulmonary arterial hypertension

Abstract: Background Patients with pulmonary arterial hypertension (PAH) have lower cerebral blood flow (CBF) and oxygenation compared to healthy sedentary subjects, the latter negatively correlating with exercise capacity during incremental cycling exercise. We hypothesized that patients would also exhibit altered CBF and oxygenation during endurance exercise, which would correlate with endurance time. Methods Resting and exercise cardiorespiratory parameters, blood velocity in the middle cerebral artery (MCAv; transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Based on the aforementioned, the purpose of this cross-over, placebo controlled, clinical trial was to investigate in a group of IPF patients, without resting hypoxemia, the acute effects of oxygen administration (fraction of inspired oxygen, FiO 2 0.40) during steady-state submaximal exercise (as compared to the delivery of medical air [sham oxygen, FiO 2 0.21]) on cerebral and skeletal muscle oxygenation and systemic hemodynamic profile and whether the above improvements coexist with enhancements in exercise duration, perception of leg fatigue, and severity of dyspnea. Considering data in patients with other pulmonary disease showing that the reduction in cerebral oxygenation is also a contributing factor to impaired exercise performance [20,23,24], we tested the hypothesis that oxygen supplementation during exercise improves cerebral oxygenation (increases cerebral-O 2 Hb and prevents the rise in HHb) and prolongs cycling duration in patients with IPF exertion-induced hypoxemia.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the aforementioned, the purpose of this cross-over, placebo controlled, clinical trial was to investigate in a group of IPF patients, without resting hypoxemia, the acute effects of oxygen administration (fraction of inspired oxygen, FiO 2 0.40) during steady-state submaximal exercise (as compared to the delivery of medical air [sham oxygen, FiO 2 0.21]) on cerebral and skeletal muscle oxygenation and systemic hemodynamic profile and whether the above improvements coexist with enhancements in exercise duration, perception of leg fatigue, and severity of dyspnea. Considering data in patients with other pulmonary disease showing that the reduction in cerebral oxygenation is also a contributing factor to impaired exercise performance [20,23,24], we tested the hypothesis that oxygen supplementation during exercise improves cerebral oxygenation (increases cerebral-O 2 Hb and prevents the rise in HHb) and prolongs cycling duration in patients with IPF exertion-induced hypoxemia.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we [5] and others [105,106] demonstrated that patients with PAH also have lower CBF and impaired regulatory mechanisms, altering the buffering of blood pressure changes and potentially explaining why patients with PAH are more prone to syncope after Valsalva-induced decreases in blood pressure [107]. At exercise, cerebral oxygenation was also markedly impaired during incremental [5,106] and endurance exercise [108], tightly correlating with the exercise capacity of patients with PAH [5]. Interestingly, oxygen supplementation significantly enhanced cerebral oxygenation, maximal workload and endurance time during exercise, attesting of its probable relevance for exercise tolerance in patients with PAH [109].…”
Section: Impaired Cerebrovascular Function and Oxygenationmentioning
confidence: 99%
“…The ΔHHbi represents the relative change in deoxygenated hemoglobin. ΔHHbi increases during hypoxia, 27 increased cerebral metabolic rate‚ and venous congestion. 20 The ΔcHbi is the only parameter that is not measured directly but calculated.…”
Section: Methodsmentioning
confidence: 99%
“…[22][23][24][25] Other instruments such as the NIRO 300 and Oxiplex TS have also been used to provide similar information, but their clinical use in cardiac surgery has not been detailed extensively. 22,[26][27][28] We hereby present the first case series in the literature describing our preliminary experience in adults using hemoglobin chromophores with complementary information from other noninvasive monitoring devices. The goal of this case series is to introduce readers to this new modality and present easily identifiable patterns that may further characterize the mechanisms of cerebral desaturation.…”
mentioning
confidence: 99%
See 1 more Smart Citation